Proposta de um método de análise da viabilidade dos modais para o transporte do carro de combate VBC Leopard 1A5BR - Lima, Luiz Cesar dos Santos (2012)
The National Mobilization is a set of activities that aims to enable Brazil to plan and execute actions in the field of National Defence toensure the security and sovereignty of the country. When it is ordered by the state organs that are part of the System of National Defense must be prepared and equipped to execute its functions. The Brazilian Army, one of these agencies, in 2006, purchased 250 armored combat vehicles, of which 216 to be distributed among their cavalry units in Brazil. The aim of this study is to present the best alternative transportation logistics to carry these tanks in a military organization, from a given scenario, with lower cost and / or time. To achieve the goal consultations through interviews and correspondence with experts in transport, military transport and armored vehicles. The consultations allowed to define the main advantages and disadvantages of transportation modes and factors relevant to transport armored vehicles, permitting the formulation of the transport network and development of an instrument feasibility of transportation modes (check list) to be applied to routes of transport. A problem of transporting armored vehicles, from a hypothetical scenario, was solved by a mathematical model with the objective of minimizing cost or time. It was concluded that the mathematical model is a tool that can aid decision making in the transport of armored vehicles, but the best choice will depend on the proper analysis of the modes of transportation available and the correct formulation and application of the instrument feasibility of transportation modes.